Gamma Knife Stereotactic Radiosurgery for Grade 2 Meningiomas - Refaat, Tamer; Gentile, Michelle; Sachdev, Sean; Dalal, Prarthana; Butala, Anish; Gutiontov, Stanley; Helenowksi, Irene; Lee, Plato; Sathiaseelan, Vythialinga; Bloch, Orin; Chandler, James; Kalapurakal, John A. (Journal of Neurological Surgery Part B: Skull Base, 2017)
Purpose This study aims to report long-term clinical outcomes after Gamma Knife radiosurgery (GKRS) for intracranial grade 2 meningiomas.Methods In this Institutional Review Board approved study, we reviewed records of all patients with grade 2 meningiomas treated with GKRS between 1998 and 2014.Results A total of 97 postoperative histopathologically confirmed grade 2 meningiomas in 75 patients were treated and are included in this study. After a mean follow-up of 41 months, 28 meningiomas had local recurrence (29.79%). Median time to local recurrence was 89 months (mean: 69, range: 47–168). The 3- and 5-year actuarial local control (LC) rates were 68.9 and 55.7%, respectively. The 3- and 5-year overall survival rates were 88.6 and 81.1%, respectively. There was a trend toward worse LC with tumors treated with radiation doses ≤ 13 versus > 13 Gy. There was no radiation necrosis or second malignant tumors noted in our series.Conclusion This report, one of the largest GKRS series for grade 2 meningiomas, demonstrates that GKRS is a safe and effective treatment modality for patients with grade 2 meningiomas with durable tumor control and minimal toxicity. Adjuvant GKRS could be considered as a reasonable treatment approach for patients with grade 2 meningiomas.
Keywords: Gamma Knife; radiosurgery; meningioma; grade 2; stereotactic